2015
DOI: 10.1523/jneurosci.0274-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prefrontal Cortex Neurogranin Enhances Plasticity and Extinction Learning

Abstract: Increasing plasticity in neurons of the prefrontal cortex (PFC) has been proposed as a possible therapeutic tool to enhance extinction, a process that is impaired in post-traumatic stress disorder, schizophrenia, and addiction. To test this hypothesis, we generated transgenic mice that overexpress neurogranin (a calmodulin-binding protein that facilitates long-term potentiation) in the PFC. Neurogranin overexpression in the PFC enhanced long-term potentiation and increased the rates of extinction learning of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Nrgn had recently been suggested as cerebrospinal fluid biomarker for AD (36,37). Forced expression of Nrgn enhances local synaptic plasticity in mice (38). Nrgn associates with the postsynaptic density (39) and with neuronal exosomes (14).…”
Section: Discussionmentioning
confidence: 99%
“…Nrgn had recently been suggested as cerebrospinal fluid biomarker for AD (36,37). Forced expression of Nrgn enhances local synaptic plasticity in mice (38). Nrgn associates with the postsynaptic density (39) and with neuronal exosomes (14).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of Ng in the hippocampus are positively correlated with hippocampus-dependent learning performance (Huang et al, 2004). Loss of Ng in mice causes an impairment of spatial learning, in addition to altering synaptic plasticity in the hippocampus (Pak et al, 2000), whereas increasing Ng levels in the prefrontal cortex facilitates memory extinction and synaptic plasticity at prefrontal glutamatergic synapses (Zhong et al, 2015). Together, these findings suggest an important role of Ng in regulating synaptic plasticity in the central nervous system.…”
Section: Introductionmentioning
confidence: 98%
“…In this context, there is a growing interest in developing novel biomarkers that would monitor other aspects of AD pathology such as for example synaptic dysfunction and neuroinflammation and two such biomarkers, neurogranin and YKL‐40, have recently emerged. Neurogranin is calmodulin‐binding postsynaptic protein regulating synaptic plasticity and learning . Several studies demonstrated that neurogranin levels are reduced in the brain but increased in CSF of AD patients .…”
Section: Introductionmentioning
confidence: 99%